Community Responses to Climate Resilience Strategies in Urban Areas Following Hurricane Induced Flooding Events - Fahri, Andi (Generasi Sains Indonesia, 2024)
This paper synthesises qualitative perspectives focusing on the impacts of climate resilience interventions in post-hurricane flooding by certain neighbourhoods. The study explores the reception of the resilience undertakings and the aluted enablers and hinderances throughout one-on-one interviews with the residents, leaders, and other stakeholders. The study thus highlights the fact that excessive bureaucracy, lack of funds and low awareness of such issues remain key factors which hinder resilience processes and their implementation. On the other hand, receptiveness from the community, good leadership, and strong relations with key stakeholders were earmarked as the main enablers increasing local participation towards practice of resilience. Some participants reported that slow decision-making processes of the government hampered the implementation of vital resilience actions. Of this contingent, those with leadership and partnership showed better preparedness and flexibility. This study alleviates a literature gap by offering a qualitative analysis of the factors that influence community reception of resilience planning efforts, particularly in urban contexts. The results highlight the need for community inclusion in resilience plans and for such plans to combat challenges such as inadequate funds and bureaucracy. Future endeavours should include raising public awareness, reducing red tape proceduralisation, and finding fixed revenue sources for improving the reliability of the built environment of communities in cities threatened by climatic disasters.